The Influence of Coastal Proximity on Mental Health in Indonesian Society - Rahman, Azizah; Sulaiman, Ahmad (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Abstract Introduction Indonesia is currently experiencing a mental health emergency and it is potentially worsening as the increase of environmental crisis. Increasing air temperatures can increase the number of people experiencing mental disorders due to environmental stress. More importantly, Indonesia is an archipelagic country, with 70% of Indonesian people live along the coast, where this area is at the lowest point on sea level and the temperature is warmer.PurposeThis research aimed to investigate the influence of coastal proximity on community’s mental health.MethodThis research used a quantitative comparative method with a total of 394 subjects who lived less than 1 to 60 km from the coastline. The subjects were selected using clustered random sampling. This study used the GHQ-12 scale to measure the mental health. The analysis was done by One Way Anova test.ResultsPeople living less than 1 km and more than 50 km from the coastline have a high level of mental health with the lowest distress levels. People living between 20 to 50 km from the coastline showed the lowest level of mental health with the highest distress scores.ConclusionThis research concluded that the closer individuals live to the coastline, their mental health is better or higher.